The Moon is Down - Steinbeck, John. (New York The Viking Press, 1942)
Without warning the Nazis invaded the town. They seized the Mayors home as their headquarters; they publicly shot the first men who rebelled against their oppresion. They were the conquerors. But the hatred was deep in the eyes of the people. Their cold, sullen silence fell like black snow, chilling the soldiers and filling them with fear. And as the conquerors nerves wore thin, they shot at black shadows in the night.
Keywords: Novel